2022
DOI: 10.1038/s41398-022-01859-4
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolic analysis in dried blood spots reveals metabolic signature in 22q11.2 deletion syndrome

Abstract: The 22q11.2 deletion syndrome (22q11.2DS) is characterized by a well-defined microdeletion and is associated with increased risk of neurodevelopmental phenotypes including autism spectrum disorders (ASD) and intellectual impairment. The typically deleted region in 22q11.2DS contains multiple genes with the potential of altering metabolism. Deficits in metabolic processes during early brain development may help explain the increased prevalence of neurodevelopmental phenotypes seen in 22q11.2DS. However, relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…These findings expand upon an earlier, more limited study of metabolic and proteomic profiling of patients with a definitive diagnosis of 22qDS (Korteling et al, 2022 ) and in the prefrontal cortex (PFC) and hippocampal (HPC) tissue of the murine model, (Wesseling et al, 2017 ) confirming the involvement of pathways previously identified but now expanded (Table 3 ) as well as the involvement and alterations of several other pathways. To our knowledge, this is the first report of the longitudinal metabolic and proteomic profiling and on the identification of unique biomarkers that might in the future be used for early diagnosis, development, and the progression of 22qDS (Fig.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings expand upon an earlier, more limited study of metabolic and proteomic profiling of patients with a definitive diagnosis of 22qDS (Korteling et al, 2022 ) and in the prefrontal cortex (PFC) and hippocampal (HPC) tissue of the murine model, (Wesseling et al, 2017 ) confirming the involvement of pathways previously identified but now expanded (Table 3 ) as well as the involvement and alterations of several other pathways. To our knowledge, this is the first report of the longitudinal metabolic and proteomic profiling and on the identification of unique biomarkers that might in the future be used for early diagnosis, development, and the progression of 22qDS (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…They also observed changes in sphingomyelin, ceramide phosphoethanolamines, tyrosine derivates, carnitines, and pantothenic acid levels (Wesseling et al, 2017 ). A more recent study identified the metabolic signature for 22qDS in dried blood spots along with the associations of these metabolomic patterns with low intellectual functioning and ASD (Korteling et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies show many diseases resembling ASD-like phenotypes often involve chromosome 15q11-q13 segments ( 12 ). Deletions and duplications of chromosomes 15q11.2, 15q13.3, 16p11.2, 22q11.2, and BP1-BP2 are among the common genetic causes of ASD ( 1 , 13 ).…”
Section: Genetic and Environmental Factorsmentioning
confidence: 99%
“…The authors suggest untargeted metabolomics as a tool for hypothesis generation and biomarker discovery in complex disease processes, based on potential compounds (urate, methionine sulfone, cortisone and 17α-hydroxypregnanolone glucuronide) and mechanisms found as potentially linked with preterm births. 92 Korteling et al 93 used untargeted metabolomics to analyse DBS samples of children and adolescents with a syndrome associated with increased risk of neurodevelopmental phenotypes including autism spectrum disorders (ASD) and intellectual impairment. The untargeted analysis identified metabolic signatures (the authors highlighted proline as a prominent distinguishing biomarker) and the metabolites were associated with the phenotypic expressions of ASD and intelligence quotient impairment.…”
Section: Very Long-chain Acylcarnitine Dehydrogenase Deficiency [Vlca...mentioning
confidence: 99%